2015
DOI: 10.1093/eurpub/cku250
|View full text |Cite
|
Sign up to set email alerts
|

Sickness absence at a young age and later sickness absence, disability pension, death, unemployment and income in native Swedes and immigrants

Abstract: Background: Sickness absence with cash benefits from the sickness insurance gives an opportunity to be relieved from work without losing financial security. There are, however, downsides to taking sickness absence. Periods of sickness absence, even short ones, can increase the risk for future spells of sickness absence and unemployment. The sickness period may in itself have a detrimental effect on health. The aim of the study was to investigate if there is an association between exposure to sickness absence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
40
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
7
40
1
2
Order By: Relevance
“…It is known from previous studies that long-term sickness absence is a prognostic marker of future absence from work, early retirement due to ill health, and mortality (3)(4)(5)(6)(7)(8)(9). Long-term sickness absence is also associated with future unemployment, financial difficulties, psychological and social problems, and social exclusion (10)(11)(12).…”
mentioning
confidence: 99%
“…It is known from previous studies that long-term sickness absence is a prognostic marker of future absence from work, early retirement due to ill health, and mortality (3)(4)(5)(6)(7)(8)(9). Long-term sickness absence is also associated with future unemployment, financial difficulties, psychological and social problems, and social exclusion (10)(11)(12).…”
mentioning
confidence: 99%
“…Sick leave is more common among groups with lower socioeconomic status (66), however, sick-leave rates are now increasing in professions requiring higher education (67). Negative outcomes of being on sick leave that have previously been studied include premature death (68), suicide (69), reoccurring sick-leave (70), disability pension (71), unemployment (11,12), low income (72), and poor physical and mental health (73). The effect of sick leave can vary depending on gender, education and immigration status (11,74), as well as age and diagnosis (10).…”
Section: Summary Of Diagnostic Criteria For Major Depressive Disordermentioning
confidence: 99%
“…Negative outcomes of being on sick leave that have previously been studied include premature death (68), suicide (69), reoccurring sick-leave (70), disability pension (71), unemployment (11,12), low income (72), and poor physical and mental health (73). The effect of sick leave can vary depending on gender, education and immigration status (11,74), as well as age and diagnosis (10). In order to facilitate comparison between sick-leave studies, they can be categorized in the structure shown in Table 2, and perspectives taken in this thesis are marked in bold (75).…”
Section: Summary Of Diagnostic Criteria For Major Depressive Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…Sick leave due to mental disorders has been found to have a negative effect on future work life, such as a higher risk of unemployment and a lower income [7][8][9]. Sick leave has also been associated with a number of adverse health outcomes, such as poor self-rated health [10,11] and early death [12].…”
Section: Introductionmentioning
confidence: 99%